2013
DOI: 10.4102/ac.v13i1.171
|View full text |Cite
|
Sign up to set email alerts
|

The brand image and performance of small and medium enterprises: How can social responsibility activities help?

Abstract: Orientation: Business social responsibility (BSR) activities may lead to benefits for small and medium enterprises (SMEs). Research purpose:To investigate how SMEs could use BSR activities to improve their brand image and business performance.Motivation for the study: In a competitive environment, SMEs face various challenges such as financial constraints, lack of resources or lack of managerial experience. BSR activities pave the way for an SME to make a positive contribution toward the environment in which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A thorough review of the literature on corporate/business social responsibility in South Africa (Jeppesen et al 2012;Turyakira et al 2012;and Rootman and Zeka, 2013) revealed that no study has empirically investigated the attitude, practice and barriers to BSR by micro enterprises in a rural environment in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…A thorough review of the literature on corporate/business social responsibility in South Africa (Jeppesen et al 2012;Turyakira et al 2012;and Rootman and Zeka, 2013) revealed that no study has empirically investigated the attitude, practice and barriers to BSR by micro enterprises in a rural environment in South Africa.…”
Section: Introductionmentioning
confidence: 99%